Odpowiedzi

2009-12-01T23:38:50+01:00
A)⅖-(1,3*⁴/₁₃-0,8)=2/5-(13/10*4/13-8/10)=4/10-(4/10-8/10)=
4/10+4/10=8/10=0,8

b)⅚-(0,6:⅜-1,6)=5/6-(6/10:3/8-16/10)=5/6-(6/10*8/3-16/10)=
5/6-(16/10-16/10)=5/6

c)14:2²/⁹-8,4*1²/₇=14:20/9-84/10*9/7=14*9/20-108/10=
63/10-108/10=-35/10=-3,5

d)(3,2+⅖):(0,5-3,2)*4½=(32/10+2/5):(-2,7)*9/2=
(32/10+4/10):(-27/10)*9/2=36/10*(-10/27)*9/2=-6

e)10,3-(-4,2)*⅙-2,5:¼=10,3-(-42/10*1/6)-2,5*4=
10,3-(-7/10)-10=10,3+0,7-10=1

f)(-⅔*1⅛+²/₉*⅜):⅛=(-2/3*9/8+2/9*3/8)*8=(-3/4+1/12)*8=
(-9/12+1/12)*8=-8/12*8=-16/3

g)(-2)³:(1,6)-(4,5*1⅔-3,75)*0,004=
-8:(16/10)-(45/10*5/3-375/100)*4/1000=
-8*10/16-(15/2-375/100)*4/1000=
-5-(750/100-375/100)*4/1000=
-5-(375/100)*4/1000=-5-15/1000=5-0,015=4,985


h)2,5+(⅔-1,8:1⅕):(-⅓)=25/10+(2/3-18/10:6/5):(-1/3)=
25/10+(2/3-18/10*5/6)*(-3)=25/10+(2/3-3/2)*(-3)=
25/10+(4/6-9/6)*(-3)=25/10+(-5/6)*(-3)=
25/10+5/2=25/10+25/10=50/10=5